Biodegradation of phenol by free and immobilised cells of locally-isolated bacteria - Aisami, Abubakar (2017)
Phenol is mainly used by the industries to produce a variety of chemical products such as resins, textiles, pesticides, plastics and explosive. Due to the wider use of phenol and other phenolic compounds by industries, this has resulted in an increased presence of these toxic compounds in the environment. In Malaysia, phenol and phenolic compounds rank among the top three scheduled wastes with thousands of tonnes being produced yearly for disposal. In Malaysia about 37.7 metric tonnes of phenol and phenol-containing wastes are produced in 2014, there is also an incident of tanker accidents Straits of Malacca in 2003 where tonnes of phenol spilt into the river and the Kapar power plant in Klang, Selangor uses coal thereby producing phenol as a by-product.These make phenol one of the environmental problem in Malaysia. Bio-removal of phenol by microorganisms especially bacteria has been demonstrated to be the most effective and economical approach compared to physio-chemical methods. The search for efficient phenol-degraders especially local sources to remediate local phenol pollution is important as indigenous bacteria usually have better survival and resilient to local geographical conditions. In this study, phenol-degrading microorganisms were isolated from local soils and water bodies. Identification was carried out using 16s rRNA gene sequencing and molecular phylogeny analysis using the Phylip software. The isolates were inoculated in mineral salt media with 0.5 g/L phenol as the sole source of carbon. Phenol degradation was determined using 4-amino antipyrine method. Physical and cultural conditions influencing phenol degradation such as pH, temperature, nature of bacteria, salinity, and nitrogen source were optimised via one-factor-at-a-time and response surface methodology (RSM). The robust and hardy Gellan gum was used for the immobilisation of bacterial cells and also the ortho and meta-pathways for phenol degradation were elucidated. The highest degradation was achieved at pH 7.5 (phosphate buffer) for all of the three isolates, with an optimum temperature of 30°C for Pseudomonas sp. AQ5-04 and Alcaligenes sp. AQ5-02 and 32.5°C for Serratia sp. AQ5-03. Ammonium sulphate was established to be the best nitrogen source at the concentration of 0.4 g/L for all three isolates and a sodium chloride concentration of 0.1 g/L for Alcaligenes sp. AQ5-02 and 0.15 g/L for Serratia sp. AQ5-03. However, Pseudomonas sp. AQ5-04 could tolerate up to 0.2 g/L of sodium chloride. This indicates that these isolates are not suitable for remediation of phenol in the marine environment. Immobilisation has reduced the incubation period from 48 h to 24 h for all three isolates, with Pseudomonas sp. AQ5-04 showing the best reusability of 22 cycles compared to 16 and 14 cycles for Alcaligenes sp. AQ5-02 and Serratia sp. AQ5-03, respectively. The immobilised cell of Alcaligenes sp. AQ5-02, Serratia sp. AQ5-03 and Pseudomonas sp. AQ5-04 can degrade up to 1900 mg/L. All the three isolates have the ability to degrade phenol both in free and immobilised cells. Immobilisation has significantly enhanced their biodegradation ability. Pseudomonas sp. AQ5-04 has the highest reusability as well as tolerating slightly high salinity. The meta pathway for phenol degradation was detected for Alcaligenes sp. AQ5-02 Pseudomonas sp. AQ5-04 while the ortho pathway was detected for, Serratia sp. AQ5-03. The accuracy and statistical analysis of the kinetic models used show that the best model was Luong for all bacterial growth curves with the lowest values for root mean square error or RMSE and adjusted Akaike Information criteria AICc, highest adjusted R2 values, and with Bias Factor and Accuracy Factor nearest to unity (1.0) for Pseudomonas sp. AQ05-04 and Serratia sp. AQ05-03, with the exception of Alcaligenes sp. AQ05-02 where the AICc value was not the lowest but the rest of the statistical analysis values still overwhelmingly pinpointing the Luong model as the best model for Alcaligenes sp. AQ05-02. The calculated value for the Luong’s constants maximal growth rate, half saturation constant for maximal growth, maximal concentration of substrate tolerated and curve parameter that defines the steepness of the growth rate decline from the maximum rate, symbolized by umax, Ks, Sm, and n were 0.10±0.02 hr-1, 0.02±0.01 g/L, 2.05±0.06 g/L and 0.80±0.20 (± 95% confidence interval) for Pseudomonas sp. AQ05-04, 0.07±0.02 hr-1, 0.02±0.01 g/L, 1.18±0.03 g/L and 1.16±0.23 for Serratia sp.AQ05-03, and 0.07±0.01 hr-1, 0.18±0.03 g/L, 1.27±0.24 g/L and 6.60±0.94 for Alcaligenes sp. AQ05-02, respectively. It appears that the highest maximum growth rate on phenol was exhibited by Pseudomonas sp. AQ05-04, while both Serratia sp.AQ05-03 and Alcaligenes sp. AQ05-02 had similar lower growth rates indicating that Pseudomonas sp. AQ05-04 showed a higher efficient growth rate on phenol.